2021
DOI: 10.3390/ijms22094312
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein 3 Promotes Osteoblast Differentiation in C2C12 Cells via Reduction of Oxidative Stress

Abstract: Metallothioneins (MTs) are intracellular cysteine-rich proteins, and their expressions are enhanced under stress conditions. MTs are recognized as having the ability to regulate redox balance in living organisms; however, their role in regulating osteoblast differentiation is still unclear. In this research, we found that the expression of MT3, one member of the MT protein family, was specifically upregulated in the differentiation process of C2C12 myoblasts treated with bone morphogenetic protein 4 (BMP4). Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…Previous studies in our lab have demonstrated that MT3 is important for osteoblast differentiation [ 40 ], and numerous in vitro studies have shown that osteogenic factors inhibit adipogenesis, while adipogenic factors hinder osteogenesis [ 41 , 42 , 43 ]. Therefore, to explore the role of MT3 in adipocyte differentiation, we induced 3T3-L1 adipocyte differentiation and examined the levels of Mt1 , Mt2 , and Mt3 by RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies in our lab have demonstrated that MT3 is important for osteoblast differentiation [ 40 ], and numerous in vitro studies have shown that osteogenic factors inhibit adipogenesis, while adipogenic factors hinder osteogenesis [ 41 , 42 , 43 ]. Therefore, to explore the role of MT3 in adipocyte differentiation, we induced 3T3-L1 adipocyte differentiation and examined the levels of Mt1 , Mt2 , and Mt3 by RT-qPCR.…”
Section: Resultsmentioning
confidence: 99%
“…Certain aspects regarding the correlation between PEEK (polyether ether ketone)’s chemical structure and the oral cavity conditions have already been demonstrated to be favorable: the ether groups (R-O-R) ensure structural flexibility, ketone groups (R-CO-R) give rigidity, while the phenylene groups are chemically unreactive. Consequently, the three functional groups give PEEK (polyether ether ketone) an excellent resistance to chemical attack, good processability, toughness, and high strength [ 3 , 81 , 83 , 84 , 85 , 86 ]. It has been pointed out that PEEK (polyether ether ketone) has a good resistance to hydrolysis [ 80 , 87 ].…”
Section: Interim Prosthetic Materials Used For Obtaining Implant-supp...mentioning
confidence: 99%
“…ROS is the main type of free radical involved in the destruction of bone remodeling 5 . ROS inhibits the expression of Runt‐related transcription factor‐2 (Runx2) and osterix, reducing osteogenic activity, while promoting the expression of osteoclast markers such as C‐Fos, Nuclear Factor of Activated T cells‐1 (NFATc1), and Tartrate Resistant Acid Phosphatase (TRAP) 6,7 . ROS may enhance the response of osteoclast precursors to Receptor Activator of NF‐κB Ligand (RANKL), and induce the production of additional osteoclastic factors, such as IL‐1, IL‐6, and IL‐7 8,9 .…”
Section: Introductionmentioning
confidence: 99%